Facades thermal insulation:: decrease of energetic consumption of buildings on Bioclimatic Zone 2 - Spinelli, Rodrigo; Mottin, Maurício Henrique; Cambeiro, Faustino Patiño; Konrad, Odorico (Sustainability in Debate, 2018)
Currently the world energy and environmental scenario is in a critical state, with increasing energy demand. Its generation still depends on exhaustible and polluting natural resources. The high electric consumption directed to the artificial climatization is the main target of the study. The purpose of this paper is to analyze the thermal insulation of the building, External Thermal Insulation Composite System (Etics), against the hot climate of the Bioclimatic Zone 2 region in the analyzed period, through normative calculations and temperature measurements in prototypes executed in masonry, in the city of Lajeado, RS, Brazil. As a result, it was obtained a reduction of 81% in the thermal transmittance (U), and 68% of the energy consumption of the prototype with Etics, which considerably interfered in the design of air conditioners. The system efficiency was evident when the internal temperature comparative graphs were analyzed, with the Etics prototype exhibiting more mild and stable temperatures, compared to the external environment and to the non-insulated prototype. The analyses demonstrate a considerably positive intervention of the Etics in the thermal performance, for Bioclimatic Zone 2.